Fitoremediación del agua para el cultivo de plantas en el vivero forestal del gad municipal del cantón Latacunga, provincia de Cotopaxi, periodo 2015 - Pastuña Curco, Klever Darío (2015)
Phytoremediation is a water decontamination method, such as TOTORA plant (Schoenoplectus californicus). It helps to decontaminate water by the ability of microorganisms capable of degradation processes to purify water quality. In this research the TOTORA was chosen for its environment adaptation, quick growth and quality. Also, It covers large areas in a short time. This method is very convenient. These kinds of plants absorb pollutants through the roots and then stored in its raw wise and use it for their metabolism and thus maximize the properties of these elements. There is a need to jealously guard the water as an essential element of life. Improper use of this resource or pollution, which undoubtedly affected further deterioration, would endanger the survival of all living things. After performing the water analysis proceeded to implement….